Development of Domestic and Foreign Industrial Enterprises in Russia - Andrei Trifonov; Alexandr Mikhalchuk; Vladislav Spitsin; Marina Ryzhkova; Lubov Spitsina; Anton Boznyakov (International Journal of Economics and Financial Issues, 2017)
The paper analyzes the Russian industry ownership structure and its dynamics for enterprises in Russian (RO), foreign (FO) and joint (JO) ownership in stable periods 2005-2008, 2009-2014, and crisis ones 2008-2009 and 2014-2015. We apply the multivariate statistical analysis of time series, including factor analysis, cluster analysis, analysis of variance. We find that raw material and low-tech industries (CA, DF, DJ, DA) continue to be the leaders by the value of shipped products in Russia. The main group of high-tech and medium-tech industries with enterprises in RO (DL, DM, DK, DG) demonstrates the average growth rates and cannot close the gap on leaders. Industry sectors with enterprises in the FO and JO behave differently. Some industries demonstrate outstripping growth, but several sectors show a slowdown and instability in the development for 2009-2014. We also define the industries which negatively react to both crises periods and require state support.